2018
DOI: 10.1128/msystems.00137-18
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplantation Beneficially Regulates Intestinal Mucosal Autophagy and Alleviates Gut Barrier Injury

Abstract: The gut microbiota plays a crucial role in human and animal health, and its disorder causes multiple diseases. Over the past decade, FMT has gained increasing attention due to the success in treating Clostridium difficile infection (CDI) and inflammatory bowel disease (IBD). Although FMT appears to be effective, how FMT functions in the recipient remains unknown. Whether FMT exerts this beneficial effect through a series of changes in the host organism caused by alteration of gut microbial structure is also no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 52 publications
6
76
1
1
Order By: Relevance
“…The results showed that RT somehow modulates the mRNA expression of genes related to immune and barrier function in the rumen epithelia of sheep with acute rumen acidosis. These results were somehow consistent with findings of Cheng et al (43), who found that fecal microbiota transplantation effectively Con, n = 5; RT, n = 5. a, b The statistical significance among 3 groups. Identical letters represent no significant difference; different letters represent significant difference.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that RT somehow modulates the mRNA expression of genes related to immune and barrier function in the rumen epithelia of sheep with acute rumen acidosis. These results were somehow consistent with findings of Cheng et al (43), who found that fecal microbiota transplantation effectively Con, n = 5; RT, n = 5. a, b The statistical significance among 3 groups. Identical letters represent no significant difference; different letters represent significant difference.…”
Section: Discussionsupporting
confidence: 92%
“…Autophagy in host cells can be influenced by the gut microbiota composition. It was shown that fecal microbiota transplantation induces an increase in autophagy-related protein levels in the intestinal mucosa of piglets, suggesting that intestinal microbiota modulation may influence mucosal autophagy [35]. Bacterial metabolites have a major effect on energy homeostasis and also on autophagy in colonic epithelial cells [36].…”
Section: Autophagy and Gut Microbiotamentioning
confidence: 99%
“…Piglets are particularly prone to ETEC K88-induced diarrhea when the bacteria adhere to the small intestinal epithelium and produce adhesins and enterotoxins, ultimately causing intestinal inflammation via activation of the nuclear factor-kappa B (NF-κB) pathway (Chandler and Mynott, 1998;Yu et al, 2017). Invasion by ETEC K88 also disrupts the colonic microflora balance in piglets (Cheng et al, 2018). Antibiotics and heavy metal compounds like zinc oxide and copper sulfate are widely used in the swine industry to treat ETEC infections.…”
Section: Introductionmentioning
confidence: 99%